The Non-amyloidal Component Region of α-Synuclein Is Important for α-Synuclein Transport Within Axons - Anderson, Eric N.; Hirpa, Delnessaw; Zheng, Kan Hong; Banerjee, Rupkatha; Gunawardena, Shermali (Frontiers in Cellular Neuroscience, 2020)
Proper transport of the Parkinson’s disease (PD) protein, α-synuclein (α-syn), is thought to be crucial for its localization and function at the synapse. Previous work has shown that defects in long distance transport within narrow caliber axons occur early in PD, but how such defects contribute to PD is unknown. Here we test the hypothesis that the NAC region is involved in facilitating proper transport of α-syn within axons via its association with membranes. Excess or A53T fPD mutant α-syn accumulate within larval axons perturbing the transport of synaptic proteins. These α-syn expressing larvae also show synaptic morphological and larval locomotion defects, which correlate with the extent of α-syn-induced axonal accumulations. Strikingly, deletion of the NAC region (delNAC) prevented α-syn accumulations and axonal blockages, and reduced its synaptic localization due to decreased axonal entry and axonal transport of α-syn, due to less α-syn bound to membranes. Intriguingly, co-expression of delNAC with full-length α-syn modulated α-syn accumulations and decreased the insoluble higher molecular weight α-syn fraction, indicating that this region is perhaps important for the dimerization of α-syn on membranes. Together, our observations suggest that under physiological conditions α-syn associates with membranes via the NAC region, and that too much α-syn perturbs axonal transport via aggregate formation, instigating synaptic and clinical pathology seen in PD.